Therapeutic Potential of Mesenchymal Stromal Cell-Derived Extracellular Vesicles in the Prevention of Organ Injuries Induced by Traumatic Hemorrhagic Shock - Valade, Guillaume; Libert, Nicolas; Martinaud, Christophe; Vicaut, Eric; Banzet, Sébastien; Peltzer, Juliette (Frontiers in Immunology, 2021)
Severe trauma is the principal cause of death among young people worldwide. Hemorrhagic shock is the leading cause of death after severe trauma. Traumatic hemorrhagic shock (THS) is a complex phenomenon associating an absolute hypovolemia secondary to a sudden and significant extravascular blood loss, tissue injury, and eventually hypoxemia. These phenomena are responsible of secondary injuries such as: coagulopathy, endotheliopathy, microcirculation failure, inflammation and immune activation. Collectively, these dysfunctions lead to secondary organ failures and multi-organ failure (MOF). The development of MOF after severe trauma is one of the leading causes of morbidity and mortality, where the immunological dysfunction plays a central role. Damage-associated molecular patterns induce an early and exaggerated activation of innate immunity and a suppression of adaptive immunity. Severe complications are associated with a prolonged and dysregulated immune–inflammatory state. The current challenge in the management of THS patients is to prevent organ injury which currently has no etiological treatment available. Modulating the immune response is a potential therapeutic strategy for preventing the complications of THS. Mesenchymal Stromal Cells (MSC) are multipotent cells found in a large number of adult tissues and used in clinical practice as a therapeutic agent for immunomodulation and tissue repair. There is growing evidence that their efficiency is mainly attributed to the secretion of a wide range of bioactive molecules and Extracellular Vesicles (EV). Indeed, different experimental studies revealed that MSC-EVs could modulate local and systemic deleterious immune response. Therefore, these new cell-free therapeutic products, easily stored and available immediately, represent a tremendous opportunity in the emergency context of shock. In this review, the pathophysiological environment of THS and in particular the crosstalk between immune system and organ function are described. The potential therapeutic benefits of MSC or their EV in treating THS are discussed based on the current knowledge. Understanding the key mechanisms of the immune deregulation leading to organ damage is a crucial element in order to optimize the preparation of EV and potentiate their therapeutic effect.